FAKTOR-FAKTOR YANG MEMPENGARUHI LIKUIDITAS PERBANKAN SYARIAH - Alfian (EKSYA : Jurnal Ekonomi Syariah, 2021)
This study was conducted to analyze the effect of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operational Costs and Operational Financing (BOPO), Inflation, and Bank Indonesia Syariah Certificates (SBIS) on the Liquidity of Islamic Banks. in Indonesia as proxied by the ratio of Financing to Deposit Ratio (FDR). This study uses monthly data, starting from January 2011 to December 2017. The data processing method used is the multiple linear regression analysis method. The results of the simultaneous regression test showed that TPF, CAR and NPF, BOPO, Inflation, and SBIS simultaneously had a significant effect on FDR. The results of the partial regression test found that the independent variables of TPF, NPF, and Inflation had a positive and partially significant effect on the dependent variable, namely FDR. Meanwhile, CAR, BOPO, and SBIS have a partially negative and significant effect on the dependent variable, namely FDR in Islamic Banking in Indonesia. The results of the regression test of the most dominant variable affecting FDR in Islamic Banking is SBIS. Based on the value of R square, it shows that the effect of the independent variable on FDR is 78.8%, so that the residual 21.2% is influenced by other variables outside this study.